2005
DOI: 10.1037/0735-7028.36.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Training Directors' Views of Number of Practicum Hours Necessary Prior to Internship Application.

Abstract: A national survey of training directors of academic programs, predoctoral internships, and postdoctoral fellowships was conducted to explore what constitutes an adequate number of practicum hours necessary to apply for internship. Training directors agreed that minimum standard hours should be set but differed on what those hours should be, with academic training directors endorsing fewer hours than directors of predoctoral internships and postdoctoral fellowships. The results raise questions about what is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Given the potential for variability in internship application preparation seminars, we have several suggestions for training and education regarding internship at the doctoral program level. Upon entering a program, students should be educated by the director of training about the predoctoral internship, and she or he should provide resources and articles that address internship expectations (e.g., Ko & Rodolfa, 2005). Students should be encouraged to think about internship early in their program and to visit the APPIC internship database.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential for variability in internship application preparation seminars, we have several suggestions for training and education regarding internship at the doctoral program level. Upon entering a program, students should be educated by the director of training about the predoctoral internship, and she or he should provide resources and articles that address internship expectations (e.g., Ko & Rodolfa, 2005). Students should be encouraged to think about internship early in their program and to visit the APPIC internship database.…”
Section: Discussionmentioning
confidence: 99%
“…Mooney (2005) found that graduate students enter internship with virtually no knowledge regarding managed care and its impact on the profession. Ko and Rodolfa (2005) asked clinical training directors and internship directors to state what an "adequate" number of practicum hours might be. They found that although there was agreement about the need to set a minimum number of hours, academic training directors endorsed fewer hours than internship directors.…”
Section: Preparation Of Internsmentioning
confidence: 99%
“…Internship directors reported that their programs spend the majority of their teaching and training time on these objectives, that they consider them most essential to the task of internship training and would rarely (with three exceptions) consider eliminating either one, and are most confident in understanding what their programs must offer to meet standards for these objectives. In sum, internship directors understand that the purpose of clinical training at the internship level is, first and foremost, to enhance and expand clinical knowledge and skills in order to prepare clinicians for clinical practice and are in line with all previous investigations of what internships understand as their mission and what teaching and training events they offer in their programs (American Psychological Association et al, 1997;Ko and Rodolfa, 2005;Lopez, Oehlert, & Moberly, 1996;Stedman, 1997;Stedman, 2007;Stedman et al, 2000;Stedman et al, 2007;Stedman et al, 2005). Hence, these two learning objectives were perceived by internship directors as central to the mission of internship training and in no need of clarification.…”
Section: Discussionmentioning
confidence: 95%